The Industrial Engineering publishing landscape - Claasen, Schalk (The South African Journal of Industrial Engineering, 2012)
Looking at the Industrial Engineering publishing landscape through the window of Google Search, an interesting panorama unfolds. The view that I took is actually just a peek and therefore my description of what I saw is not meant to be comprehensive. The African landscape is empty except for the South African Journal of Industrial Engineering (SAJIE). This is an extraordinary situation if compared to the South American continent where there are Industrial Engineering journals in at least Brazil, Peru, and Chile. In Australia The Industrial Engineer was published for some 50 years commencing in the 1950s. The Institute of Industrial Engineering Australia